2014
DOI: 10.1152/jn.00680.2013
|View full text |Cite
|
Sign up to set email alerts
|

Natural scenes in tactile texture

Abstract: Sensory systems are designed to extract behaviorally relevant information from the environment. In seeking to understand a sensory system, it is important to understand the environment within which it operates. In the present study, we seek to characterize the natural scenes of tactile texture perception. During tactile exploration complex high-frequency vibrations are elicited in the fingertip skin, and these vibrations are thought to carry information about the surface texture of manipulated objects. How the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
153
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(158 citation statements)
references
References 77 publications
(93 reference statements)
5
153
0
Order By: Relevance
“…Three different texture samples were selected from a previously used dataset (7,20): one fine texture (wool gabardine), one coarse texture (upholstery), and a dot pattern (2-mm interdot spacing). Texture profiles (obtained by profilometry) were used as inputs to the model (with surfaces approximated as rigid).…”
Section: Simulated Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different texture samples were selected from a previously used dataset (7,20): one fine texture (wool gabardine), one coarse texture (upholstery), and a dot pattern (2-mm interdot spacing). Texture profiles (obtained by profilometry) were used as inputs to the model (with surfaces approximated as rigid).…”
Section: Simulated Experimentsmentioning
confidence: 99%
“…Coarse object features, such as edges and corners, are reflected in spatial patterns of activation in slowly adapting type I (SA1) and rapidly adapting (RA) fibers, which are densely packed in the fingertip (3,4). At the same time, interactions with objects and surfaces elicit high-frequency, low-amplitude surface waves that propagate across the skin of the finger and palm and excite vibration-sensitive Pacinian (PC) afferents all over the hand (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Bensmaïa et al attempted to measure these high frequency components as a finger was sliding over the surface of a material by using a Hall-effect transducer attached to the finger [6]. Similarly, the propagated vibratory information was acquired using a laser Doppler velocity meter [7,8], microphones [9], accelerometers [10], and PVDF films [11] attached to the finger close to the tip, as well as a microphone [12] on the forearm. Although these vibrations in the adjacent skin originate from the vibratory deformations of the finger pad, these methods were not to measure the deformations of the individual finger pad.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of texture and vibrotactile perception, the phases of the skin vibrations were less influential, and the power or intensity of the spectral density in the frequency domain are considered important [6,8,[23][24][25]. Some researchers have demonstrated that virtual textures or surfaces can be presented even without a representation of the phase information of the vibratory signals [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of natural scene statistics has proven to be a powerful approach for understanding neural coding within audition and vision, but has yet to be generally applied to the somatosensory system, although some work has been done on texture (Ritt et al, 2008;Manfredi et al, 2014). In the context of somatosensation, the way in which the animal's tactile sensors sample the environment will obviously play an important role in determining the tactile sensory data it will acquire.…”
Section: Introductionmentioning
confidence: 99%